Effectiveness of Instructional Program on Patients’ Nutritional Habits for Patients with Peptic Ulcer - AL Hamad, Haider Abd AL Ameer Twair; Hassan, Huda Baker (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: The aim of the current study is to determine the effectiveness of the instruction program on nutritional habits of patients with peptic ulcer, and to find out the relationship between these habits and their socio-demographic characteristics.Methodology: A quasi-experimental design study was carried out at Al-Diwaniya Teaching Hospital. non-probability sampling which including 30 patients for the studygroup and 30 patients for the control group. The program and study instrument were prepared from a literature review and previous research, the validity of the questionnaire was determined through a panel of (11) experts and the reliabilitythrough a pilot study, the questionnaire's reliability was determined by computing the Alpha Correlation Coefficient todetermine the instrument's internal consistency, the statistical and analyzed the data was conducted through thedescriptive and inferential statistical analysis procedure.Results: The study's findings showed that the instruction program had a positive effect on patients' nutritional habits, and a significant statistical association betweenthe patient's employment, level of education, and monthly income and the effectiveness of the instruction program regarding nutritional habits.Conclusion: The instruction program had a positive effect on patients with peptic ulcers and changed their nutritional habits among the study group.Recommendations: The study recommends increasing the patient’s knowledge regarding nutritional habits and explaining diet through periodic seminars, television programs, and social media and the use of the presents program for the all patients with peptic ulcer.